Optimizing precision rhinoplasty: comprehensive preoperative planning with nasal computed tomography for functional and aesthetic enhancement - Pawel Szychta (SpringerOpen, 2024)
Abstract Background The evolving field of rhinoplasty increasingly recognizes the importance of clinical expertise over routine preoperative nasal computed tomography (CT) for planning surgical interventions. This study evaluates the clinical utility of preoperative nasal CT in enhancing the precision of open structured rhinoplasty, focusing on both functional and aesthetic outcomes without compromising patient safety through unnecessary radiation exposure. The study aimed to assess the impact of preoperative nasal CT on surgical planning and intraoperative maneuvers. Methods A prospective cohort study involved patients undergoing open structured rhinoplasty with or without preoperative nasal CT. Participants were divided into a study group, receiving preoperative nasal CT, and a control group, undergoing rhinoplasty without such imaging. Surgical modifications were tailored based on CT findings, with outcomes evaluated through postoperative nasal airflow and aesthetic satisfaction. Results The study included 205 patients in the CT group and 514 in the control group, with comparable demographics. The CT group demonstrated significant improvements in nasal breathing and higher aesthetic satisfaction postoperatively, with a notable decrease in the NOSE score and an increase in the ROE score compared to the control group. Minor complications were observed in a small percentage of the CT group, showcasing a nuanced approach to addressing individual anatomical variations. Conclusions Preoperative nasal CT in open structured rhinoplasty significantly enhances surgical precision, optimizing functional and aesthetic outcomes. This study underscores the utility of preoperative CT in individualized surgical planning, suggesting its pivotal role in the advancement of rhinoplasty practices. Future research should explore long-term benefits and further validate these findings across diverse populations.